Susceptibility profile of a Brazilian yeast stock collection of Candida species isolated from subjects with Candida-associated denture stomatitis with or without diabetes - Sanitá, Paula Volpato; de Oliveira Mima, Ewerton Garcia; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Elsevier, 2013)
Objective: This study investigated the susceptibility of 198 clinical isolates of Candida species against caspofungin, amphotericin B, itraconazole, and fluconazole. Study Design: Suspensions of the microorganisms were spread on Roswell Park Memorial Institute (RPMI) agar plates. Etest strips were placed on the plates, and the minimal inhibitory concentration (MIC) was read after incubation (48 h at 37°C). Data were analyzed by a factorial analysis of variance and a 2 × 2 post hoc test (α = .05). Results: C glabrata showed the highest MIC values (P < .001) against caspofungin, itraconazole, and fluconazole. For amphotericin B, the MIC values of C tropicalis and C glabrata (P = .0521) were higher than those of C albicans (P < .001). Itraconazole was the least effective antifungal; 93.3% of the C glabrata isolates, 3.3% of the C albicans, and 1.3% of the C tropicalis were resistant. All microorganisms were susceptible to caspofungin and amphotericin B. Conclusions: Caspofungin and amphotericin B should be recommended as an effective alternative for the management of oral Candida infections when treatment with topical or other systemic drugs has definitely failed. © 2013 Elsevier Inc. All rights reserved.